0083 The use of multi modal and hybrid simulation in the training of multi disciplinary professionals. (2nd November 2015) - Trimble, Alice; Thomas, Richard; Attoe, Nicola; Palmer, Kate
Abstract : Background: Simulation can provide safe, realistic learning environments for repeated practice, underpinned by feedback and objective metrics of performance. 1 Technical skills are often the main focus of simulation sessions whilst non-technical skills e.g. communication with patients/relatives and other team members are often neglected. Non-technical skills are essential for providing good safe medical practice. 2, 3 The UK Foundation Programme Curriculum 4 provides information and guidance for newly qualified doctors and those involved in their education: This combines traditional medical training elements with communication and consultation skills, patient safety and teamwork. Several pieces of research have shown the importance of training as part of a multi disciplinary team. Falcone et al. stated, 5 "Training of a multidisciplinary team in the care of paediatric trauma patients can be enhanced and evaluated through the use of high-fidelity simulation. Improvements in team performance using innovative technology can translate into more efficient care with fewer errors." Therefore we recognise the importance of inter professional multi disciplinary training in acute medicine. We propose to set up a realistic learning environment for multi disciplinary professionals including the use of multi-modal, hybrid simulation using both actors and mannequins. These simulation sessions will target technical and non-technical skills encompassing patients and other team members as well as traditional mannequin training. Methodology: 30 FY1 doctors, Nurses, Health Care Support Workers and Paramedics will attend a simulation session in July 2015. Eight sessions will be held in the Winchester Simulation Suite set up as Resuscitation Area of an Emergency Department (ED). To facilitate a realistic learning environment, these sessions will combine 'multi-modal' and 'hybrid' components. Initial assessment and management will be done on a 'human' patient played by an actor. At a given point in the scenario the patient will have a cardiac arrest at which a traditional mannequin will be used. The simulation scenario will be 'hybrid' combining the cardiac arrest medical management and non-technical skills including communication (during and post resuscitation) with "relatives" of the patient. Results: Results will be taken from pre and post questionnaires and feedback sessions. Perceived confidence and skills levels will be recorded and analysed. Themes emerging from the feedback sessions and a free text box will be analysed. Potential impact: We are evaluating hybrid simulation for its potential as a training tool for junior doctors and non-medical professionals. We hope technical and non-technical skill levels will increase post sessions, thus improving medical practice, team working and patient safety. References: Kneebone R. Simulation in surgical training: educational issues and practical implications. Med Educ. 2003:37 Stroud L, Cavalcanti B. Hybrid simulation in knee arthocentesis: improving fidelity in procedure training. J Gen Intern Med. 2013:28 Resus Council. Advanced Life Support Manual 6 th edition January 2011 NHS Foundation Programme Curriculum 2012 with amendments for 2014/2015 www.foundationprogramme.nhs.uk Accessed on 20/05/2015